FUTURE CHANGES IN SEASONAL-MEAN PRECIPITATION OVER WEST AFRICA UNDER THE REPRESENTATIVE CONCENTRATION PATHWAYS (Nigerian Journal of Technology, 2017)
This study analysed the  future changes in seasonal-mean precipitation over West Africa during the mid (2040-2065) twenty first century using the Norwegian Earth System Model version 1 (NorESM1-M). The NorESM1-M has ~1.89° x 2.5° horizontal atmospheric resolution and 26 vertical levels. The skill of the model in reproducing the observed seasonal-mean precipitation distribution was evaluated for the historical period (1980-2005) using satellite derived precipitation data from the Global Precipitation Climatology Project. Using three possible future levels of atmospheric greenhouse gas concentrations - the Representative Concentration Pathways (RCPs) of 2.6Wm-2, 4.5Wm-2 and 8.5 Wm-2, we calculated the projected changes in seasonal-mean precipitation over West Africa for the mid-twenty first century. The projected changes show that the transition to dry season (September-October-November) will experience the highest amounts of increase. Overall, RCP 4.5 projects higher levels of precipitation change compared to the other two RCPs. This points to a non-linear effect of intensified greenhouse forcing on precipitation over West Africa; suggesting that after a particular level of greenhouse gas concentrations further increase may have little or no effect on the regions precipitation. http://dx.doi.org/10.4314/njt.v37i1.31